Medical Compliance and Childhood Asthma on the Mexican Border: "They Think You Are God" - Schwartz, Norah (Frontera Norte, 2017)
Often chronic and potentially life threatening, asthma is one of the most common of all childhood illnesses. It is a known risk factor tor pneumonia, as well as tor other acute respiratory infections (ARI). ARIs have become a major focus of study for medical anthropologists. However, little ethnographic research has been conducted on the treatment of chronic childhood respiratory illness. Because of the worldwide increase in antibiotic resistance, understanding how and why treatment choices are made is imperative. This research focuses on life experiences and treatment strategies of mothers of young children with asthma residing in Tijuana, Mexico. Management of illness takes place not only in the clinic but also in relation to home health, pharmaceutical, and traditional medical care. Is there a standard definition of medical compliance followed by all physicians? How does the definition of "compliance" from the perspective of the physician compare to that of the patient? Because children with chronic illness are prone to acute infections, studies of this nature can provide useful insight into treatment choice for both chronic illness and infectious disease. RESUMEN Con frecuencia, el asma es una amenaza crónica y potencial a la vida, v es una de las enfermedades más comunes de la infancia; también es un conocido factor de riesgo en casos de neumonía y de otras infecciones respiratorias agudas, las cuales se han convertido en tema central de estudio para los antropólogos médicos. Para este análisis, hemos realizado una pequeña investigación etnográfica del tratamiento de las enfermedades respiratorias crónicas de la infancia. Debido al incremento global en la resistencia antibiótica, es imperativo entender cómo y por qué se toman decisiones sobre las opciones de tratamiento. Esta investigación se concentra en experiencias de vida y estrategias de tratamiento que las madres dan a los niños residentes de Tijuana, México, que padecen asma. El manejo de la enfermedad no sólo tiene lugar en la clínica, sino también en su relación con la casa, el cuidado farmacéutico y los cuidados tradicionales. ¿Existe una definición estándar del procedimiento médico seguido por los doctores? ¿Cómo es la definición de "proceder" desde la perspectiva del médico en comparación con la del paciente? Debido a que los niños con enfermedades crónicas son propensos a infecciones agudas, estudios de esta naturaleza pueden ofrecer un conocimiento útil sobre opciones de tratamiento tanto para enfermedades crónicas como infecciosas.